Catholicism and the Support for European Integration: A Critique of the Methodological Underpinnings - Rosita Garškaitė (Chrześcijaństwo-Świat-Polityka)
It has long been argued that a special relationship between Catholicism and European integration exists. Yet, the scholarly discussion of its meaning has seldom gone beyond statistical analyses that show robust correlations, but cannot provide an understanding of why and when Catholics tend to choose commitment to European Union over skepticism or indifference to it. Three philosophical arguments are presented in the paper which indicate the flaws of positivist research and show how an interpretivist approach could shed light on the topic studied.